EMPLOYING UNDERAGE CHILDREN IN STUDY INTERNATIONAL LAW AND ISLAMIC LAW - Astuti, Mirsa; lubis, syofiaty; ginting, lilawati (Proceeding International Seminar of Islamic Studies, 2023)
The aim of this research is to provide protection to children who become child labourers. Child protection is all activities to ensure and protect children and their rights so that they can live, grow and develop. In fact, many children are found in various countries as workers or laborers. Therefore the United Nations (UNICEF) and ILO (International Labor Organization) organizations on child labor issued policies on child labour. The ILO has issued legal instruments in the form of conventions which are then ratified in every country to become regulations. The ILO convention aims to completely eliminate all forms of child labour, although this is very difficult to do given the current conditions. Islamic law does not explicitly explain the employment of minors, but Islam provides special protection for children so that they do not lose their rights. Based on the background above, the problem arises how international law efforts to protect child labor and what is the view of Islamic law on child labour. The research method used is normative juridical, namely conducting library research by examining library materials or secondary data as a basis for research by conducting a search of regulations or conventions and literature related to the problem under study.